Uncovering hedge fund skill from the portfolio holdings they hide - Vikas Agarwal; Wei Jiang; Yuehua Tang; Baozhong Yang (University of Cologne, Centre for Financial Research (CFR), 2011)
This paper studies the confidential holdings of institutional investors, especially hedge funds, where the quarter-end equity holdings are disclosed with a delay through amendments to the Form 13F and are usually excluded from the standard databases. Evidence supports private information as the dominant motive for confidentiality. Funds managing large risky portfolios with non-conventional strategies seek confidentiality more frequently. Stocks in these holdings are disproportionately associated with information-sensitive events or share characteristics indicating greater information asymmetry. Confidential holdings exhibit superior performance up to twelve months. The probability of SEC approval is associated with the fraction of portfolios seeking confidentiality and the filer's track records.
Keywords: G10; G19; 330; confidential treatment; ownership disclosure; 13F holdings; hedge funds